Peculiarities of the prevalence of partial secondary adentia and its complications in children and adolescents - S. I. Doroshenko; S. M. Savonik (Kazimierz Wielki University, 2020)
Rationale. The high prevalence of anomalies, partial adentia and its complications determine the importance of searching new optimal means of prevention, orthodontic and orthopaedic treatment, taking into account the age peculiarities of a child's body during its formation. Objective: To study the prevalence, etiological factors and features of the clinical progression of partial secondary adentia and its complications in children and adolescents in order to develop optimal means of prevention, orthodontic and orthopaedic treatment. Materials and methods. 2276 people aged from 4 to 17 years were examined during the temporary, mixed and permanent dentition periods, in order to study the prevalence of partial secondary adentia and its complications in children and adolescents. The examinations were conducted in the organized child care of Kyiv (kindergartens, schools) and at the Department of Orthopedic Dentistry and Orthodontics of the private higher educational institution "KyivMedicalUniversity". All patients were divided into 3 age groups depending on the period of formation of the dento-maxillaire system. Results. According to the results of the examinations, the high prevalence of partial secondary adentia was detected in both posterior and anterior dentition, in particular, among the examined 2276 children, partial secondary adentia was detected in 359 people, including 115 children with the defect of the anterior area and 264 people had the defect of posterior dentition. The causes of partial secondary adentia in the examined children were: the removal of temporary and permanent teeth caused by caries and its complications - 278 (77.4%) cases, the second place takes - the loss of teeth caused by traumatic injuries - 34 children (9.3%). Deformity of dental arches was diagnosed in 278 people (77,43%) among the children with partial secondary adentia, indicating the high prevalence of such a pathology due to untimely dental care, in particular, the lack of prosthetic treatment. Conclusions. The occurrence of partial secondary adentia in children and adolescents caused by caries and its complications, as well as traumatic injuries in 77.4% of cases in the absence of prosthetic treatment leads to complications in the form of deformities of dental arches. Carrying out temporary teeth maintenance procedure until the term of their physiological change, as well as taking timely treatment, prevention and prosthetic measures will aid the harmonious development of a child's dento-maxillaire system and prevention of complications.